Effects of Enzyme Volumes on Hydrolysis and Fermentation for Ethanol Production From Leftover Cooked Rice - Chen, Xikai; Zhao, Yujia; Chen, Boyang; Su, Wang; Zhang, Zhengxian; Liu, Yanxu; Xu, Xiaobin; Tang, Junhong; Hou, Pingzhi; Han, Wei (Frontiers in Bioengineering and Biotechnology, 2021)
This study aimed to utilize the enzymatic hydrolysis of leftover cooked rice (LCR) for fermentative ethanol production. Effects of glucoamylase volumes (V1: 5 U/g, V2: 25 U/g and V3: 50 U/g) on the performance of LCR hydrolysis was also evaluated. It was found that the highest chemical oxygen demand (COD) of 77.5 g/L and reducing sugar (RS) of 34.6 g/L were achieved at V3, respectively. The LCR hydrolysate obtained from enzymatic hydrolysis was then used as feedstock for ethanol fermentation. Higher ethanol production was obtained when RS increased from 18.7 g/L (V1) to 23.2 g/L (V2). However, lower ethanol production was found when RS further increased to 34.6 g/L (V3) probably because too high RS concentration led to the inhibition on the yeast. The maximum ethanol production and yield were 21.1 g/L and 0.3 g ethanol/g LCR, respectively. (Conclusion) The LCR could be a promising substrate for fermentative ethanol production for industrial application.